Rumen Fermentation and Performance of Lactating Dairy Cows Affected by Physical Forms and Urea Treatment of Rice Straw - Gunun, P. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The aim of this study was to determine the effect of different physical forms and urea treatment of rice straw on feed intake, rumen fermentation, and milk production. Four, multiparous Holstein crossbred dairy cows in mid-lactation with initial body weight (BW) of 409±20 kg were randomly assigned according to a 4×4 Latin square design to receive four dietary treatments. The dietary treatments were as follows: untreated, long form rice straw (LRS), urea-treated (5%), long form rice straw (5% ULRS), urea-treated (2.5%), long form rice straw (2.5% ULRS) and urea-treated (2.5%), chopped (4 cm) rice straw (2.5% UCRS). Cows were fed with concentrate diets at a ratio of concentrate to milk yield of 1:2 and rice straw was fed ad libitum. The findings revealed significant improvements in total DM intake and digestibility by using long and short forms of urea-treated rice straw (p<0.05). Ruminal pH was not altered among all treatments (p>0.05), whereas ruminal NH(3)-N, BUN and MUN were found to be increased (p<0.01) by urea-treated rice straw as compared with untreated rice straw. Volatile fatty acids (VFAs) concentrations especially those of acetic acid were decreased (p<0.05) and those of propionic acid were increased (p<0.05), thus acetic acid:propionic acid was subsequently lowered (p<0.05) in cows fed with long or short forms of urea-treated rice straw. The 2.5% ULRS and 2.5% UCRS had greater microbial protein synthesis and was greatest when cows were fed with 5% ULRS. The urea-treated rice straw fed groups had increased milk yield (p<0.05), while lower feed cost and greater economic return was in the 2.5% ULRS and 2.5% UCRS (p<0.01). From these results, it could be concluded that 2.5% ULRS could replace 5% ULRS used as a roughage source to maintain feed intake, rumen fermentation, efficiency of microbial protein synthesis, milk production and economical return in mid-lactating dairy cows.